POTENSI ANTIOKSIDAN HASIL FRAKSINASI EKSTRAK ETANOL Phaseolus vulgaris L - Vincentius Y Utomo; Yayuk Andayani; Erin Ryantin Gunawan (Jurnal Penelitian Pendidikan IPA, 2018)
A research on the antioxidant potential of ethanol extract Phaseolus vulgaris L. fractination. The aims study to know fraction had been antioxidant potential and dominant compound at extract fraction. Antioxidant potential fraction is polar fraction and its IC50 is 158 ppm. A dominant compound at nonpolar, semipolar dan polar fraction is phenolic compound. Polar fraction had a greatest percentage phenolic compound (42%).